How Indonesian Polytechnic Students Navigate TOEFL’s Demands - Romadhon, Romadhon (Journal of English for Academic and Specific Purposes (JEASP), 2025)
Indonesian Polytechnics' implementation of the TOEFL as a graduation requirement highlights issues between the demands of global employability and the fairness of vocational education. While previous research has criticized standardized testing in higher education, the present research addresses an essential gap in investigating its implications in technical education, where English language proficiency is supplementary to the skills that are practiced in vocational education. This qualitative case study explores polytechnic students' perceptions of the role, issues, and benefits of TOEFL test as a graduation requirement. Data were collected using questionnaires (n=60) and semi-structured interviews (n=10) at a single Serang-Banten Polytechnic, and thematically analyzed to take into account how institutional policy intersects with students' academic and career trajectories. Findings suggest that 72% of the students pragmatically endorsed TOEFL as a career necessity, driven by market demands. However, systemic limitations, such as content mismatch, inadequate infrastructure, and socioeconomic inequality, reduced performance and increased exam anxiety. In particular, 60% struggled with grammar and vocabulary, while 55% reported hearing unfamiliar accents in listening sections. Despite challenges, 89% identified the benefits of TOEFL, such as the acquisition of metacognitive skills and job prospects. The study contributes new insights by situating high-stakes testing in vocational studies, countering homogenized discourses of EFL learners. The study calls for context-sensitive language policies that mediate global standards and local contexts. This research hopes to educate policymakers and educators interested in balancing employability objectives with inclusive pedagogies in Indonesia's technical education sector.